Organic cations in halide perovskite solid solutions: exploring beyond size effects - Minussi, F. B. [UNESP]; Silva, R. M. [UNESP]; Moraes, J. C.S. [UNESP]; Araújo, E. B. [UNESP] (Royal Society of Chemistry (RSC), 2024)
Halide perovskites are a class of materials of consolidated optoelectronic and electrochemical applications, reaching efficiencies compared to established materials in respective fields. In this scenario, the design and understanding of composition-structure-property relations is imperative. In solid solutions containing mixed cations, some direct relations between the sizes of the substituents and the properties of perovskites are generally observed. However, in several cases, these relations are not observed, implying that other characteristics of these cations play a major role. Despite its importance, this understanding has not been comprehensively deepened. To address this issue, we synthesized and characterized the structure, electrical behavior, and stability of methylammonium lead iodide-based perovskites with equal amounts of the substituents guanidinium, ethylammonium, and acetamidinium. These three large organic cations have essentially equal sizes but other remarkably different characteristics, such as the number of N-H bonds, intrinsic dipole moment, and order of C-N bonds. Herein, we show that these cations have dramatically different effects over important fundamental and applied properties of resulting perovskites, including the orthorhombic-to-tetragonal and tetragonal-to-cubic phase transitions, microstructural development, ionic conductivity, I-V hysteresis, electronic carrier mobility, and stability against light-induced degradation. These effects are correlated with the characteristics of the large substituent cations and help pave the way for a better rational chemical design of halide perovskites.